Koniáš a Langhans(en): Dvě postily čtené v první polovině osmnáctého století - Šindelářová, Martina (Lidé města, 2008)
Reflecting the religious and political situation of Bohemia in the first half of the 18th century, this contribution attempts to deliver a comparative analysis of two religious texts. The first is a Catholic postil by one of the most influential Czech-writing Jesuits, Antonín Koniáš, and the second its Protestant counterpart, written by a German Lutheran preacher Christian Langhans, which was translated into Czech, published (and distributed) by religious emigrants. The author considers these two postils to be a convenient source of information on the two church-enforced life (and beyond) ideals. On one side, there is the Catholic, official, state-promoted set of beliefs, on the other side, the concealed, differentiated and persecuted non-Catholic one. The first part of this paper informs the reader about the political situation and matters of popular reading in the period in question. Furthermore, it presents a hypothesis of the French researcher Marie-Élizabeth Ducreux concerning a possible link between non-Catholic identity and reading activity. The second part of the text is a segment of the author’s text analysis concentrated on the preachers’ dealing with issues of reading itself, and various aspects of their religious beliefs. Within the dogmas analysed, the issues raised are the sacraments and their treatment, afterlife, God’s grace (especially the matters of faith vs. deeds, spiritual rebirth, saints and chosen ones), religious behaviour (sacred persons, time, objects and deeds) and the Church as an institution.